Working And Musculoskeletal Disorders Posture On Concrete Workers Of Production Division At PT. X Bali - Suryawan, Komang Y; Handoyo, Henry R; Tanudjaja, George (JOURNAL OF WIDYA MEDIKA JUNIOR, 2021)
Introduction: Musculoskeletal disorders are injuries that Affect the musculoskeletal systemthat can be the caused or aggravated by the working environment. Factors that can causemusculoskeletal disorders are exertion of force, repetition, and awkward posture. Awkwardposture held too long in the same position will cause injuries and complaints , which in turnwill Decrease the productivity for the workers and the company. Purpose: The aim of the study is to examine the correlation between working posture andmusculoskeletal disorders on concrete workers of the production division in PT. X Bali. Method: This study is an observational analytical study with cross-sectional design,participated by 43 concrete workers of production division using consecutive samplingtechnique. The study was held at PT X's concrete plant on Jl. Prof. Dr. Ida Bagus Mantra No.2461, Gianyar, Bali from 15th July to 17th July. Working posture was measured with RapidEntire Body Assessment (REBA) and the level of musculoskeletal disorder was measured with Nordic Body Map (NBM). Both variables were Analyzed using Kendall's Tau-C to Determine the correlation between working posture and musculoskeletal disorders. Results: Most workers had moderate risk of working posture measured with REBA (46.5%).Using the NBM method, most workers had moderate levels of musculoskeletal disorders.(46.5%). The distribution of MSDs on the body part are mostly located on the shoulder andhip. Analysis of correlation between working posture and musculoskeletal disorder results in(p < 0.001) and (r = 0.769). Conclusion: that there is a significant correlation between work posture with musculoskeletalcomplaints in concrete factory workers of the production unit at PT. X Bali.